TINDAK TUTUR ILOKUSI DAN DEIKSIS RUANG DAN WAKTU DALAM DIALOG FILM RUMAH MASA DEPAN KARYA DANIAL RIFKI - Mispita Dwi Purnama Sari, Eva; Rukiyah, Siti; Fitriani, Yessi (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2025)
The formulation of the problem in this research is "What are the illocutionary and deictic speech acts in the dialogue of the film Rumah Masa Depan by Danial Rifki?". This research aims to describe the form of illocutionary and deictic speech acts in the dialogue of the film Rumah Masa Depan by Danial Rifki. The method used in this research is a descriptive qualitative research method. The data in this research are the utterances in the dialogue of the film Rumah Future. The results of this research show that the illocutionary and deictic speech acts in the film Rumah Masa Depan by Danial Rifki consist of assertive, directive, expressive illocutionary and space and time deixis. The research results concluded that there are several forms and functions of illocutionary speech acts, namely assertive stating, suggesting, boasting and complaining. The directive function is ordering, ordering, and requesting. The expressive function is to say thank you, express condolences, blame and praise. The forms of space (place) deixis are locative and demonstrative deixis. The forms of time deixis are present time, future time and past time. Keywords: Speech acts, Illocution, Deixis, Film